A channel model for power line communication using 4PSK technology for diagnosis: Some lessons learned. (February 2018) - Mishra, Madhav; van Riet, Maarten
Highlights: Modern smart grid and smart metering concepts are based on reliable digital communications. The power cable is used for energy supply and as data communication distribution network so that it does not require the installing of new cables providing advantage of low infrastructure cost. A motive to achieve greater bit rates and communication that is more reliable over power lines has been underlining factor for this work. A complete channel model of a PLCs ystem (i.e. Transmission line, Coupling and Communication) and evaluation of BER of PSK when corrupted with noise. Abstract: Modern smart grids and smart metering concepts are based on reliable digital communications. The absence of dedicated communications media, such as telephone lines or fibre optics within a power line network, can make transmission challenging. Electrical power companies are interested in implementing an overall communicating power line network. The power line communication (PLC) system uses the electric power distribution grid as a data transmission medium. The data transmission problem resulted due to poorly developed Medium Voltage Network of PLC Channel Model and challenges in data transmission technology, so this hampers better performance. This paper studies PLC over a medium voltage network with a goal of achieving greater bit rates and communication that is more reliable over power lines. It presents a complete channel model of a PLC system and evaluation of Bit Error Rate (BER) of Phase Shift Keying (PSK) when corrupted with noise. It calculates the number of sections between two substations to determine signal loss. The PSK modulation scheme in simulation is experimentally found to be more robust against such power line distortions as noise for point-to-point transmission. The model and calculations use Matlab and QUCS.